Interrogating postfeminism : gender and the politics of popular culture - Tasker, Yvonne, 1964-; Negra, Diane, 1966- (Durham, [N.C.] : Duke University Press, 2007)
Brings feminist critique to bear on contemporary "postfeminist" mass media culture, analyzing phenomena ranging from female action films to the "girling" of aging women in productions such as the movie Something's Gotta Give and the British television series 10 Years Younger.
Postfeminism and popular culture : Bridget Jones and the new gender regime / Angela McRobbie -- Mass magazine cover girls : some reflections on postfeminist girls and postfeminism's daughters / Sarah Projansky -- Living a charmed life : the magic of postfeminist sisterhood / Hannah E. Sanders -- "I hate my job, I hate everybody here" : adultery, boredom, and the "working girl" in twenty-first-century American cinema / Suzanne Leonard -- Remapping the resonances of riot grrrl : feminisms, postfeminisms and "processes" of punk / Anna Feigenbaum -- Killing Bill : rethinking feminism and film violence / Lisa Coulthard -- Queer eye for the straight guise : camp, postfeminism, and the fab five's makeovers of masculinity / Steven Cohan -- What's your flava? race and postfeminism in media culture / Sarah Banet-Weiser -- The fashion police : governing the self in what not to wear / Martin Roberts -- Divas, evil black bitches, and bitter black women : African American women in postfeminist and post-civil-rights popular culture / Kimberly Springer -- Subjects of rejuvenation : aging in postfeminist culture / Sadie Wearing.
Includes bibliographical references (pages [311]-330) and index.
ENH
Trim Education
Keywords: Feminist theory; Popular culture; English language; Sex role; Mass media and women